(3TQM GdLeds - (3CHh GdNSf WGgQ Hf CMeO Hf HGHTGP GdfMhis; (3GdLQLGfj , YHO GdbGgQ Hf YHO GdQMef Hf eMeO, CHh HcQ,J (B471 (3g` s ((3CMeO Hf eaVd s)
(3ChdgG (B:s
(3HGH eG jfUQa heGdGjfUQa (B: (3CUd GdCSeGA GdUQa , hEfeG JeJfY ef GdUQa dYdg YGQVI s
(3BNQgG (B:s
(3aMPahG Gdfhf aUGQ YdeG , hYdjg GdHjJ GdPi CfTOg s
(3GdfSNI HgG MhGTs
(3cJHJ GdYfGhjf HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B48 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B310s
Keywords: (3GdfMhs